2009
DOI: 10.1001/archpsyc.66.1.22
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Splicing, Methylation State, and Expression Profile of Tropomyosin-Related Kinase B in the Frontal Cortex of Suicide Completers

Abstract: A reduction of TrkB.T1 expression in the frontal cortex of a subpopulation of suicide completers is associated with the methylation state of the promoter region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
134
2
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 210 publications
(153 citation statements)
references
References 71 publications
(101 reference statements)
4
134
2
5
Order By: Relevance
“…Previous studies had shown differences in DNA methylation 9 and histone modifications 5 in the TrkB promoter and microRNA binding 10 in TrkB-T1 3′UTR sequences between controls and suicide completers. However, the results from these previous studies suggested that additional mechanisms were necessary to explain the extreme decrease in TrkB-T1 expression observed in frontal cortical areas of suicide completers.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Previous studies had shown differences in DNA methylation 9 and histone modifications 5 in the TrkB promoter and microRNA binding 10 in TrkB-T1 3′UTR sequences between controls and suicide completers. However, the results from these previous studies suggested that additional mechanisms were necessary to explain the extreme decrease in TrkB-T1 expression observed in frontal cortical areas of suicide completers.…”
Section: Discussionmentioning
confidence: 96%
“…8 Previous studies point to a change in the level of TrkB expression in suicide completers. [9][10][11] The TrkB gene, located on chromosome 9, encodes three receptors of neurotrophins, characterized by specific 3′UTR sequences. TrkB gene products are involved in neurotransmission, calcium release, synaptic plasticity, and cell survival, 12 processes whose altered functions have been implicated in the neurobiology of suicide.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Decreased astrocyte mRNA and/or protein expression of GFAP (Braun et al, 2009), aquaporin 4 (Rajkowska and Stockmeier, 2013), connexins (Miguel-Hidalgo et al, 2014;Rajkowska and Stockmeier, 2013;Verkhratsky et al, 2015b), plasmalemmal glutamate transporters (Bernard et al, 2011;Ernst et al, 2009), and glutamine synthetase (Barley et al, 2009;Bernard et al, 2011;Rajkowska et al, 1999;Sequeira et al, 2009) in postmortem brain samples from depressed suicides. Evidence of astroglial dysfunction and immune activation in postmortem brain samples from depressed suicide victims (Nagy et al, 2015;Torres-Platas et al, 2014a;TorresPlatas et al, 2011).…”
Section: Humanmentioning
confidence: 99%